Miniinvasive Face and Body Lifts Closed Suture Lifts or Barbed Thread Lifts - Serdev, Nikolay (IntechOpen, 2013)
The biggest buzz in the facial and body lifting beautification and rejuvenation category is by far around mini-invasive scarless techniques. They are presented by suture and thread lifts. Both suture and thread lift techniques have many unique properties. For example, young patients do not want to be scarred with classic open face liftings. Also, for Asians, Afro-Americans, and Latino-Americans, who have higher percentage of keloids, these are the preferred non-scarring cosmetic surgery methods. Scarless mini-invasive lifting techniques, such as suture and thread lifts, need proper explanation and public access. This will be the first scientific book that could clear the false public belief that transcutaneous suture and thread lifts are one and the same method.